Murabahah Sukuk structure: the shari'ah challenges and the way forward - Adam Sa'ad, Auwal; Ibrahim, Uzaimah; Mohammad Deen, Mohd Napiah (University of Turin - Italy, 2016)
Murabahah Sukuk is an Islamic trust contract which includes a disclosure of the original cost and the mark up. Murabahah in Islamic jurisprudence means a contract of sale for the equivalent price of the subject matter which includes its cost along with a known additional profit. The paper discusses issues related to Murabahah Sukuk financing. It also provides the structural overview of Murabahah in terms of Sukuk issuances. The paper highlighted three different ways of structuring Murabahah Sukuk, it looks into the structure of Murabahah for asset acquisition, Murabahah with Inah transaction and lastly Murabahah with tawarruq transaction. The paper concluded that according to the general rules of Shari’ah, Murabahah Sukuk should not be traded at secondary market due to the fact that it involved the sale of debt which is forbidden. However, Murabahah Sukuk might be negotiated at the secondary market if it forms a small part of a larger portfolio comprising other negotiable instruments such as Ijarah Sukuk, Musharakah, and Mudarabah Sukuk certificates.